Comparative study of morphophysiological responses among cowpea and long beans plants under drought stress condition (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Syafriani E, Susilo KR, Sayekti RS, Widyawan MH, Khoirunnisa NS, Rahmadhani M. 2022. Comparative study of morphophysiological responses among cowpea and long beans plants under drought stress condition. Biodiversitas 23: 5507-5518. Long bean plants are generally more susceptible to drought stress than cowpea plants. One of the promising solutions is through plant breeding to produce genetically modified long bean plants resistant to drought stress by crossing with cowpeas. Parental selection is the initial stage of the plant breeding program. This stage was performed by selecting parental varieties based on the desired superior characteristics, including morphological and physiological characteristics, as well as, yield production. Unfortunately, the comparison between long bean plants and cowpea plants is not well-studied. Therefore, the aim of this study was to analyze the morphophysiological similarities and differences between long beans and cowpeas to withstand drought stress. A two-factorial randomized block design was used in this study and consisted of 2 factors (plant varieties and type of drought stress). The plant varieties used in this study are 7 long bean plants and 7 cowpea plants. While the level of drought stress were: T0 (watering every day), T1 (every 5 days), and T2 (every 10 days). The observational data from morphophysiological characters indicated that long bean plants were more tolerant to drought stress than cowpea plants. Interestingly, one of the cowpea varieties (C2) had the highest proline contents (20.27 µmol/gram of leaves sample) compared to other varieties. Hence, the C2 variety can be considered a candidate for further studies. Meanwhile, all the tested 7 varieties of long bean plants showed varying adaptability, possibly due to the genetic diversity of each variety against drought stress.